Pengaruh Literasi Keuangan Digital terhadap Perilaku Menabung dan Perilaku Berbelanja pada Generasi Z - Alysa, Alysa; Muthia, Fida; Andriana, Isni (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine and analyze the effect of digital financial literacy on saving behavior and shopping behavior in generation Z. This research uses a quantitative method with a questionnaire as a research instrument. The population in this study focused on undergraduate students in the Management Department of the Faculty of Economics at Sriwijaya University and there were 1,004 people. The research sample is determined by the technique purpose sampling and calculated using the formula slovin, so that as many as 91 students participated in this study. The data analysis technique used in this study is descriptive statistical analysis and using multiple linear regression Sturctural Equation Modelling-Partial Least Squared (SEM-PLS) withsoftware WarpPLS 7.0. The results of this study indicate that digital financial literacy has a positive and significant effect on saving behavior and shopping behavior in generation Z. Keywords: digital financial literacy, saving behavior, and shopping behavior